Alteration of crop rotation in continuous Pinellia ternate cropping soils profiled via fungal ITS amplicon sequencing. (25th March 2019) - He, Z.; Chen, H.; Liang, L.; Dong, J.; Liang, Z.; Zhao, L.
Abstract: Pinellia ternata is a traditional Chinese herb that has been shown to suffer from continuous cropping. Deterioration in continuous P. ternata cropping soils and the effect of alteration of crop rotation on the soil were evaluated by using Illumina high‐throughput sequencing technology. Soil physicochemical properties and fungal diversity were significantly lower in continuous P. ternate cropping soil compared with those of uncultivated soil. In contrast, significant increases in soil factors and fungal diversity were detected after the continuous cropping soil was subjected to rotational cropping treatments, indicating a remediation effect of crop rotation on continuous cropping soil. Moreover, with the extension of wheat cropping in the rotations, fungal richness and most physicochemical properties exhibited a significantly increasing trend, suggesting that the remediation effect of crop rotation could be enhanced by extending the cropping of break crops. Furthermore, compared with those of continuous cropping soils, microbes that were potentially beneficial to P. ternate were enriched in the rhizosphere by rotational cropping, whereas micro‐organisms that supposedly lead to soil deterioration were suppressed. Redundancy analysis indicated that Podospora and Alternaria were the major microbes that were responsible for increasing soil physicochemical properties; by contrast, the deterioration in soil fertility was mainly attributed to Fusarium micro‐organisms. Significance and Impact of the Study: Knowledge of deterioration in continuous Pinellia ternate cropping soils and how crop rotations alter the deteriorated soil is still limited, especially regarding the presence of fungi and soil fertility. This research found remediation effects of crop rotation on continuous P. ternate cropping soils and indicates that these effects could be enhanced by extending the cropping of break crops. Community shifts between the continuous and rotational cropping soils and the associated changes in soil fertility will have a considerable impact on the diagnosis of obstacles to continuous P. ternate cropping and enhancement of the remediation effects of crop rotation. Abstract : Significance and Impact of the Study: Knowledge of deterioration in continuous Pinellia ternate cropping soils and how crop rotations alter the deteriorated soil is still limited, especially regarding the presence of fungi and soil fertility. This research found remediation effects of crop rotation on continuous P. ternate cropping soils and indicates that these effects could be enhanced by extending the cropping of break crops. Community shifts between the continuous and rotational cropping soils and the associated changes in soil fertility will have a considerable impact on the diagnosis of obstacles to continuous P. ternate cropping and enhancement of the remediation effects of crop rotation.